Income inequality among indigenous people dependent on traditional agroforestry system in Indian Himalayas - PANDEY, D K; ADHIGURU, P; DE, H K; UPADHYAY, A D; RADHAKRISHNAN, K (The Indian Journal of Agricultural Sciences, 2021)
There is increasing concern about unequal distribution of income and wealth especially in developing economies, and to address this issue, there is greater thrust for inclusive development in the recent years. In this context, this paper looks into growing income inequality among the forest dwellers based on the empirical study conducted in North Eastern Hill (NEH) states of India. The primary data were collected through survey and personal interview covering a sample of 500 forest dweller households’ sampled during 2016-17 from 52 villages located across six NEH states (Arunachal Pradesh, Manipur, Meghalaya, Mizoram, Nagaland and Tripura). Further, various options of income generation by providing equal access to resources has been dealt in the paper. It was observed that the shifting cultivation (SC) remains the main source of livelihood in all the studied sites. The clear-cut inter-state income disparities among the forest dwellers were demonstrated by Gini ratios. The high variation in Gini ratios indicates higher disparities in nonfarm income and it may be because of unequal opportunities for non-farm activities. In addition, other factors which are contributing significantly to income inequality are socio-personal factors, policies and programmes on SC management. The understanding on the role played by such factors would greatly facilitate in evolving appropriate policy perspectives for reducing economic inequality through measures like increasing investment in human capital and thus ensuring a stable farm economy in this region.